Effects of Different Milling Methods on the Quality of Whole Wheat Flour - DENG Chong, HU Xiuting, LUO Shunjing, LIU Chengmei (Shipin Kexue)
To investigate the effect of milling equipment on the quality of whole wheat flour, four whole wheat flours with similar average particle sizes were obtained by direct crushing methods (hammer cyclone mill, gear mill, and low-temperature impact mill) and back addition method (Chopin mill), and their nutritional compositions, polyphenol contents, damaged starch contents, and gelatinization properties were evaluated. The particle size distribution of the resulting brans and the rheological properties of dough made from each of the four whole wheat flours were analyzed. The results showed that back addition had less damaging effect on bran than direct crushing. Among the three direct crushing methods, the particle size of bran ground by low-temperature impact mill was the smallest (118.00 μm). The soluble dietary fiber and free polyphenol contents of whole wheat flour ground by low-temperature impact mill were 2.22% and 48.11 mg/100 g, respectively, which were significantly higher than those of all three other flours. The relative content of damaged starch in whole wheat flour prepared by the back addition method was 3.85%, which was significantly lower than that of the direct crushing methods. Moreover, the former had better gelatinization properties and viscoelasticity. The results of this study provide a theoretical basis for the preparation and application of high-quality whole wheat flour.